Pengaruh teknik pencampuran bahan cetak alginat terhadap stabilitas dimensi linier model stone dari hasil cetakan Effect of mixing methods of alginate impression material on liniear dimensional stability of stone cast - Elizabeth Mailoa; M. Dharmautama; Peter Rovani (Journal of Dentomaxillofacial Science, 2012)
The aim of this study was to evaluate the influence of mixing technique of dental impression materials to lineardimension stability on stone cast. Fifteen stone cast formed of pouring alginat impression material (Hydrogum 5,Zhermack) obtained from maxillary typodont (Frasaco, Italy) as master model containing four metal pillars in squarelocated in area of second premolar teeth (left and right), and two in the second molar area (left and right). Mixingtechniques were done manually and mechanically (full dan semi automatic) and by pouring with dental stone type IV(Prostone-21, BMP Formula). The results are depicted of 5 models for each mixing techniques. Measurements weremade in four parameters (ac, bd, a1b1 and c1d1) of 8 reference points on metal pillars. For this study data wasanalyzed using one-way Anova statistical test with level of significance at p <0.05 and processed with SPSS v.17. Ofthe four parameters measurement on each model, there was statistically significant processed differences of 3parameters (ac, a1b1 and c1d1), whereas one parameter (bd) had no statistically significant differences (p = 0.375). Itwas concluded that the mixing technique of fully automatic mixer shows better results in terms of dimensional stabilitycompared to the manual mixing technique and semi automatic mixer.